Weill Cornell medicine : a history of Cornell's medical school - Gotto, Antonio M., Jr; Moon, Jennifer E. (Cornell University Press, 2016)
This work is a story of continuity and transformation. Cornell medical school has been a leader in education, patient care, and research-from its founding as Cornell University Medical College in 1898, to its renaming as Weill Cornell Medical College in 1998, and now in its current incarnation as Weill Cornell Medicine.